PSEUDOMONAS AERUGINOSA: EMERGING THREAT TO POST OPERATIVE WOUND INFECTION. - Pranjal Nema; Prashant Parmar; Narendra Babu; Anushi Hardaha; Amardeep Rai (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background - . In the recent condition, the growing incidence of P. aeruginosa has been increasing in  post operative wound infection and becoming more serious problem  in developing countries because of lack of general hygienic measures and mass production of low quality antiseptic : The aim  of this study was to determine the prevalence of Pseudomonas aeruginosa in  postoperative wound  infection and its susceptibility pattern.MethodologyStudy design- Retrospective observational Study.Study Centre- Bundelkhand Medical College, Sagar, Madhya PradeshStudy duration- September 2021 to June 2022.Methods and material –This is a record based study of 10 month duration. 252 patients were enrolled for the study and their post operative wound swab received were processed for identification of bacterial pathogens .Result –Out of 252 wound swabs, 80(34.7%) were P. aeruginosa, followed by Escherichia coli (52/22.6%), Klebsiella spp.(46/20%), Staphylococcus aureus(35/15.2%), Proteus spp.(13/5.6%), Acinetobacter spp. (4/1.7%).There was no growth in (22/8.7%) wound swabs.Interpretation & conclusions -Our study shows that P. aeruginosa was most prevalent (34.7%) the pathogens isolated from the surgical wounds. The primary reason for this increase in postoperative infection rate with prolonged preoperative hospitalization may be the colonization of patients with hospital-acquired resistant microorganisms.